Akses Pangan Lansia Perempuan Kepala Keluarga di Kelurahan Kumpulrejo Salatiga, Indonesia: Food Access Elderly Women Head Household in Kumpulrejo Salatiga, Indonesia - Eza Media Arlan; Theresia Pratiwi Elingsetyo Sanubari; Firdhan Aria Wijaya (Amerta Nutrition, 2023)
Background: Food security exists when everyone has access to sufficient, safe, nutritious food to maintain a healthy and active life. There are still food-insecure groups at the global and national levels, even though almost every country has already regulated food security. Older women's household headship with physical limitations, the stigma in society, and mainly the patriarchal culture surrounding them create boundaries for them to do various jobs in the domestic and public sphere to fulfill their daily needs. Objectives: By exploring women's intersectionality, this research aimed to seek the narration of the older woman as the head of the household in Kumpulrejo, Salatiga, and how they access their food. Methods: Qualitative method with participatory observation was used to understand more about their activities. Meanwhile, this research also conducted an in-depth interview to gather participants' information. Five elderly female household headship in Kumpulrejo were randomly recruited. Results: Elderly women household headship in Kumpulrejo in their old age still had problems accessing food. However, participants had various strategies for fulfilling daily food, so they were still in good condition. In the social environment, participants still mingle with the community, regardless of age and social status. Participants' ownership of kitchens and clean water still needed to be in better condition, thus increasing the risk of experiencing infections or other diseases. Conclusions: Elderly female households had easy access to food because of their various strategies, such as borrowing from local vegetable vendors to meet their daily food needs.